1998
DOI: 10.1366/0003702981943680
|View full text |Cite
|
Sign up to set email alerts
|

Laser-Induced Breakdown Spectroscopy for Polymer Identification

Abstract: Laser-induced breakdown spectroscopy has been applied to polymer samples in order to investigate the possibility of using this method for the identification of different materials. The plasma emission spectra of high-density polyethylene (HDPE), low-density polyethylene (LDPE), polyvinyl chloride (PVC), polyethylene terephthalate (PET), and polypropylene (PP) have been studied. Spectral features have been measured—for example, the 725.7 nm chlorine line, the 486.13 mm Hβ line, and the 247.86 nm carbon line—who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(72 citation statements)
references
References 7 publications
3
65
0
2
Order By: Relevance
“…Sattmann et al 358 applied the LIBS technique to investigate the possibility of using this method for the identification of different materials. They studied the plasma 503 Pasquini et al Vol.…”
Section: Chemometrics Applicationsmentioning
confidence: 99%
“…Sattmann et al 358 applied the LIBS technique to investigate the possibility of using this method for the identification of different materials. They studied the plasma 503 Pasquini et al Vol.…”
Section: Chemometrics Applicationsmentioning
confidence: 99%
“…This results demonstrated that the ratio intensity of CN/C and Ca/C in arabica coffee can be used as a marker. For organic materials, measuring both atomic and molecular emission lines and their intensity ratios are favorable for discrimination between organic materials [12][13][14][15][16][17]. The results clearly demonstrate the feasibility of application to the quantitative spectrochemical analysis of coffee using laser induced plasma spectroscopy.…”
Section: Figurementioning
confidence: 96%
“…With recent advances in broadband spectrometers and chemometric analysis techniques, the identification of non-metals has become increasingly widespread with LIBS. LIBS has been used for the identification of polymers (43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57), thermoplasts (58)(59)(60), and other organic compounds (61,62), including explosives (34)(35)(36)(37)(38)(39)(40)(41)(42)(63)(64)(65). Figure 4 shows the LIBS spectra of various thermoplastic polymers from McMaster-Carr acquired with a commercial LIBS system (Applied Photonics, Ltd).…”
Section: Identification Of Materialsmentioning
confidence: 99%